2014
DOI: 10.1021/jz500759x
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic CO2 Reduction with a Homogeneous Catalyst in Ionic Liquid: High Catalytic Activity at Low Overpotential

Abstract: We describe a new strategy for enhancing the efficiency of electrocatalytic CO2 reduction with a homogeneous catalyst, using a room-temperature ionic liquid as both the solvent and electrolyte. The electrochemical behavior of fac-ReCl(2,2'-bipyridine)(CO)3 in neat 1-ethyl-3-methylimidazolium tetracyanoborate ([emim][TCB]) was compared with that in acetonitrile containing 0.1 M [Bu4N][PF6]. Two separate one-electron reductions occur in acetonitrile (-1.74 and -2.11 V vs Fc(+/0)), with a modest catalytic current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 51 publications
(70 reference statements)
5
110
3
Order By: Relevance
“…These data contrast with a previous report studying a non-coordinating anion that generates a single reduction wave. 5 Collectively, these observations support the interpretation that ligand exchange is the underlying cause of multiple reduction processes, which is more probable for the complex in ionic liquid with a stronger coordinating anion. If the total current is used to find the diffusion coefficient for a two-electron transfer to all electroactive species, D = 1.8 × 10…”
Section: Microelectrode (Me) Electrochemistry Of Re(bpy)(co) 3 CL In supporting
confidence: 57%
“…These data contrast with a previous report studying a non-coordinating anion that generates a single reduction wave. 5 Collectively, these observations support the interpretation that ligand exchange is the underlying cause of multiple reduction processes, which is more probable for the complex in ionic liquid with a stronger coordinating anion. If the total current is used to find the diffusion coefficient for a two-electron transfer to all electroactive species, D = 1.8 × 10…”
Section: Microelectrode (Me) Electrochemistry Of Re(bpy)(co) 3 CL In supporting
confidence: 57%
“…43 We found that when neat [emim]-[TCB] (TCB = tetracyanoborate) is used as both the solvent and electrolyte for the electrocatalytic reduction of CO 2 to CO with the homogeneous catalyst, fac-ReCl(bpy)(CO) 3 (bpy =2,2′-bipyridine), the onset potential for catalytic CO 2 reduction is reduced by ∼0.45 V, compared to when CH 3 CN is used as a solvent with tetrabutylammonium hexafluorophosphate ([TBA][PF 6 ]) supporting electrolyte. 43 Importantly, we found that the rate constant for the CO 2 reduction reaction also increased by a factor of ∼40× in [emim][TCB] compared to in CH 3 CN.…”
Section: •−mentioning
confidence: 99%
“…43 We found that when neat [emim]-[TCB] (TCB = tetracyanoborate) is used as both the solvent and electrolyte for the electrocatalytic reduction of CO 2 to CO with the homogeneous catalyst, fac-ReCl(bpy)(CO) 3 (bpy =2,2′-bipyridine), the onset potential for catalytic CO 2 reduction is reduced by ∼0.45 V, compared to when CH 3 CN is used as a solvent with tetrabutylammonium hexafluorophosphate ([TBA][PF 6 ]) supporting electrolyte. 43 Importantly, we found that the rate constant for the CO 2 reduction reaction also increased by a factor of ∼40× in [emim][TCB] compared to in CH 3 CN. It is clear that the enhancement effect invoked by the imidazolium-based IL is different from enhancement effects previously reported in the presence of alkali or alkaline-earth metals; that is, these mono-or divalent metal cations can either improve the catalytic rate constant 44,45 or reduce the catalytic onset potential, 46 while the IL can do both simultaneously.…”
Section: •−mentioning
confidence: 99%
See 1 more Smart Citation
“…Imidazolium-based salts, composed merely of ions, are a kind of novel medium for many chemical processes. In recent years, increasing attempts have been made to use imidazolium-based salts as the solvents, electrolytes and catalysts for CO 2 electroreduction [8][9][10][11][12]. In the salt 1-butyl-3-methyimidazolium tetrafluoroborate (BMIMBF 4 ), CO 2 was reduced on Ag electrode at À2.0 V (vs. Ag wire) at 50 C [13].…”
Section: Introductionmentioning
confidence: 99%